Quality and Consumer Acceptance of Ready to Drink Horse Mango (Mangifera foetida Lour.) Juice - Sapbua, Dudsadee; Thorarit , Thippika; Palasuwan, Saowapan (Journal of Food Health and Bioenvironmental Science, 2023)
Horse mango (Mangifera foetida Lour.) fruit is rich in nutrition and is characterized by soft pulp-like mango that is suitable to prepare for ready-to-drink juice. The purpose of this study was to examine the physical properties, chemical properties, microbiological test, sensory evaluation and consumer acceptance test of the horse mangoes’ pulp and juice. Ready-to-drink Horse mango juice with 3 concentrations of pulp (20, 40 and 60%) was pasteurized and poured into glass bottles. The results showed that the physical properties of Horse mango pulp were observed at L*(68.78), a*(-13.24), b*(50.26), pH (3.37) and Total Soluble Solids (15.17 oBrix). The content of chemical quality of Horse mango pulp reported carbohydrate, protein, fat, ash, vitamin C per 100 g of pulp as 12.67 g, 0.74 g, 0.48 g, 0.95 g, 29.98 mg, respectively and beta-carotene as 0.86 mg/kg. In reference to the Horse mango juice, the result of the coloring content was shown as b* values (yellowness) increased with a higher amount of Horse mango pulp related to beta-carotene (the yellow pigment). The microbiological content of the 3 concentrations of Horse mango juice aligned to the Thai Community Product Standard (TCPS) 701/2557 because of pasteurization (90 °C 10 min) during the juice productions. The ready-to-drink at 40% of Horse mango juice received the highest score on all attributes (color, odor, flavor, taste and overall liking) and was analyzed for chemical content; carbohydrate, protein, fat, ash, vitamin C per 100 g of juice as 21.50 g, 2.27 g, 0.04 g, 0.33 g, 10.29 mg, respectively and beta-carotene content as 0.61 mg/kg. For the acceptance of 100 consumers, consumer accepted 70% of juice products and decided to buy ready-to-drink Horse mango juice products at 66%. However, many consumers are still unfamiliar with Horse mango therefore adding another juice for example, pineapple and orange juices could obtain more acceptance.